2021
DOI: 10.3390/ijerph18147606
|View full text |Cite
|
Sign up to set email alerts
|

Italians Are the Fastest 3000 m Open-Water Master Swimmers in the World

Abstract: Background: It is well known that athletes originating from a specific region or country can master specific sports disciplines (e.g., East-African runners in long-distance running). In addition, physical and athletic performance are the result of an interaction between genetic, environmental and epigenetic factors. However, little is known about on what determines sports success and performance for long-distance master swimmers such as origin. The aim of the study was to investigate the participation and perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Contrary to our prediction, European athletes did not perform similarly when observing overall race time. This can be explained by the IRONMAN® race distribution worldwide, 9 with the highest number of races occurring in North America. There are 11 IRONMAN® races in the United States of America, whereas there are only 20 in Europe.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrary to our prediction, European athletes did not perform similarly when observing overall race time. This can be explained by the IRONMAN® race distribution worldwide, 9 with the highest number of races occurring in North America. There are 11 IRONMAN® races in the United States of America, whereas there are only 20 in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…The observed performance decline with age in males and females followed the expected physiological and functional capacity of aged participants and the peak performance in endurance sports of older male and female athletes. 9 , 10 , 11 , 12 , 13 , 14 , 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that Italians are among the best in this sport discipline is not accidentally. A very actual study investigating 9247 female and male swimmers competing between 1986 and 2019 in the 3000 m openwater swimming Master World Championships found that female and male swimmers from Italy were the fastest during this period of 27 years and 15 editions all over the world [22]. A potential explanation that swimmers from Italy and Germany are the best in the world in this sports discipline could be their national efforts.…”
Section: Discussionmentioning
confidence: 99%